2006
DOI: 10.1016/s0022-5347(05)00211-9
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Technique Does Not Improve Cancer Detection as an Initial Prostate Biopsy Strategy

Abstract: Although saturation prostate biopsy improves cancer detection in men with suspicion of cancer following a negative biopsy, it does not appear to offer benefit as an initial biopsy technique. These findings suggest that further efforts at extended biopsy strategies beyond 10 to 12 cores are not appropriate as an initial biopsy strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(107 citation statements)
references
References 20 publications
5
102
0
Order By: Relevance
“…8,9 Increasing the number of transrectal cores at initial biopsy does not appear to significantly improve yield. 10,11 Eichler et al 8 pooled data from 68 studies and found a significant improvement in cancer detection moving from the standard sextant scheme to a 12-core approach. However, there was no benefit to further increasing the number of cores taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Increasing the number of transrectal cores at initial biopsy does not appear to significantly improve yield. 10,11 Eichler et al 8 pooled data from 68 studies and found a significant improvement in cancer detection moving from the standard sextant scheme to a 12-core approach. However, there was no benefit to further increasing the number of cores taken.…”
Section: Discussionmentioning
confidence: 99%
“…For each biopsy core, the template coordinate and the offset from base were recorded. Biopsy regions included posterior prostate (3,4,12,13,21,22), posterior lateral (2,5,11,14,20,23), anterior lateral (1,6,9,10,15,16), anterior apex (19,24), and TZ (7,8,17,18) After completion of all sampling, patients underwent cystoscopic evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…1 This approach has its limits because in 25% to 30% of patients with PCa the neoplastic tissue is not included in the samples. 2 Moreover in patients with persistently increased PSA and negative PB, the repetition of biopsies does not increase the detection rate of PCa, which indeed decreases progressively. 3 Because of the additional number of samples there is a significant risk of complications (infection, bleeding, acute urinary retention), anxiety and social-sanitary costs.…”
mentioning
confidence: 95%
“…5 We concluded that saturation biopsy improves the diagnostic yield for repeat biopsy, but does not improve results of initial biopsy, so we recommended its use only for the repeat-biopsy population. 6 We previously reported that parasagittal biopsies in the repeat biopsy population had low yield with respect to cancer detection, and that unique parasagittal cancers were rarely (not a single case in our series of 100 patients) found during repeat biopsy. We found that no cancers identified during that study were located exclusively in the parasagittal regions of the prostate and determined that focused sampling of the lateral regions of the prostate could optimize the sensitivity of repeat prostate biopsy.…”
Section: Introductionmentioning
confidence: 52%